Karya Seni Grafis yang Menarik dan Kreatif melalui Teknik Cukil - Laura Christina Luzar (Bina Nusantara University, 2011)
Relief printing is the most demanding printing until now. Through the linocut, it can produced interesting artwork of relief printing. Besides the processing was easy and simple, this printing technique is easy to be understood in a relatively short time. The most important thing in relief printing is perseverance, accuration, and creativity. It can also bring forward the expression through the resulting work of printmaking, so that the relief printing becomes an alternative media to convey the message. By the relatively low cost, anyone could begin to learn this printing technique. Almost the whole working process was done manually, with a drop of equipment. Starting from the process of image planning, cutting process, until the printing process, all of these phases could be done without the support of developing technologies. Many opinions said that the rapidly developing technologies make the work easier, but instead several aesthetics value could not be achieved by sophisticated technology.